Application of The Question and Answer Method in Learning The Material on Angel Duties in Grade VII Students of MTS Miftahul Ulum Singosari - Aulia Faizatuz Zahro; Lailatul Lutfiyah; Ahmad Ma'ruf (Jurnal Syntax Transformation, 2026)
Active, learner-centered instruction has become a global priority in contemporary education; yet Islamic Religious Education (PAI particularly abstract, faith-based material such as the duties of angels is still frequently delivered through teacher-centered lectures that limit student participation and conceptual understanding. Although prior studies have examined the question-and-answer method in PAI, most focus on measurable learning outcomes in general and rarely describe, in depth, how the method operates when applied to faith-related material at the Madrasah Tsanawiyah level; this constitutes the research gap addressed by the present study. This study aims to describe the application of the question-and-answer method in learning the material on the duties of angels and to analyze its contribution to students’ classroom engagement and understanding. Employing a qualitative descriptive case-study design, the research was conducted with 28 seventh-grade students at MTs Miftahul Ulum Singosari who were selected through purposive sampling. Data were collected through participant observation, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman interactive model of data reduction, data display, and conclusion drawing, with credibility strengthened through source triangulation and member checking. The findings indicate that the question-and-answer method increased students’ activeness, enthusiasm, and understanding, encouraged them to express opinions and pose questions, and fostered more effective two-way teacher–student interaction, although low learner confidence and uneven academic ability remained challenges. The study offers a context-specific account of interactive, constructivist PAI instruction and provides practical guidance for madrasah teachers seeking to strengthen student-centered learning of faith-based material.